2020
DOI: 10.1101/2020.09.08.288241
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide Chromatin Accessibility is Restricted by ANP32E

Abstract: Genome-wide chromatin state underlies gene expression potential and cellular function. Epigenetic features and nucleosome positioning contribute to the accessibility of DNA, but widespread regulators of chromatin state are largely unknown. Our study investigates how control of genomic H2A.Z localization by ANP32E contributes to chromatin state in mouse fibroblasts. We define H2A.Z as a universal chromatin accessibility factor, and demonstrate that through antagonism of H2A.Z, ANP32E restricts genome-wide DNA a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 72 publications
3
11
0
Order By: Relevance
“…In the latter scenario H2A.ZΔC, present only at its promoter proximal locations, would render these sites more accessible to nucleases. Such a scenario is in good agreement with the report that chromatin accessibility is increased genome-wide at promoter regions by H2A.Z (40), what is antagonized by ANP32E, the chaperone catalyzing its eviction engaging the C-terminal tail of H2A.Z (26). It will be of interest to determine which scenario explains the striking global differences.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the latter scenario H2A.ZΔC, present only at its promoter proximal locations, would render these sites more accessible to nucleases. Such a scenario is in good agreement with the report that chromatin accessibility is increased genome-wide at promoter regions by H2A.Z (40), what is antagonized by ANP32E, the chaperone catalyzing its eviction engaging the C-terminal tail of H2A.Z (26). It will be of interest to determine which scenario explains the striking global differences.…”
Section: Discussionsupporting
confidence: 91%
“…For example, as revealed by MNase-Seq, H2A.Z binding destabilizes local nucleosome structure in ES cells, leading to decreased nucleosome occupancy and increased chromatin accessibility particularly at enhancers (12). A similar observation has been made recently, showing that H2A.Z deposition creates wide ATAC-Seq positive promoter regions in mouse fibroblasts genome-wide (40). In other studies, unusually labile H2A.Z containing nucleosomes, i.e.…”
Section: Introductionsupporting
confidence: 86%
“…H2A.Z accumulates at estrogen response elements that are bound by FOXA1 and loss of H2A.Z impairs both FOXA1 binding and polymerase recruitment. ANP32E is a chromatin chaperone that regulates the genomic localization of H2A.Z to control locus-specific chromatin state dynamics (16). In recent work, we showed that ANP32E antagonizes H2A.Z installation, such that ANP32E loss causes a global increased H2A.Z enrichment, heightened chromatin accessibility and amplified TF-binding at open sites, in cultured mouse fibroblasts (16).…”
Section: Resultsmentioning
confidence: 99%
“…We recently defined the histone chaperone protein ANP32E as a genome-wide regulator of chromatin accessibility in mouse fibroblasts (16). ANP32E functions to modulate the installation/removal of H2A.Z from chromatin, regulating chromatin remodeler activity and limiting chromatin accessibility.…”
Section: Introductionmentioning
confidence: 99%
“…Success has also been reported adapting CUT&RUN for use in S. cerevisiae (Skene and Henikoff, 2017), Drosophila (Ahmad and Spens, 2019;Uyehara and McKay, 2019), Arabidopsis (Zheng and Gehring, 2019), mouse germ cells (Ernst et al, 2019;Menon et al, 2019;Prakash and Barau, 2021) and mouse and human embryos (Inoue et al, 2018;Zhang et al, 2019). Thus far, CUT&Tag has been applied to assay enrichment of modified histones in plant and mammalian tissues (Bartosovic et al, 2021;Kaya-Okur et al, 2019;Murphy et al, 2020;Tao et al, 2020;Wang et al, 2021;Wu et al, 2021;Yu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%